(untitled) (Bangladesh Journal of Botany, 2019)
The effect of gamma irradiation (100, 200, and 300 Gy) and NaCl (60 and 120 mM) on peroxidase (POD) and polyphenol oxidase (PPO) activities in Sids-1 and Sakha-93 wheat cultivars were investigated. POD and PPO activities increased significantly with increasing NaCl concentrations, and the maximal activity increased at 120 mM NaCl, while PPO activity was higher than POD at the same concentration of NaCl in both the two cultivars. POD and PPO isozymes profile revealed a total of six bands, whereas all of them are variable and exposed the effect of gamma ray and sodium chloride with different genetic response of the two wheat cultivars. The expression level of POD gene in Sakha-93 cultivar was more than in Sids-1. While it was more pronounced at 120 mM NaCl combined with gamma irradiation dose 300 Gy. Gamma ray can be used as a useful tool for gene expression in plants and salt tolerance could be attributed to the constitutive induced antioxidant gene, leading to more efficient enzyme stimulation and protection in wheat.